SERUM FREE LIGHT CHAIN RATIO IN CORRELATION WITH SERUM PROTEIN ELECTROPHORESIS IN MULTIPLE MYELOMA PATIENTS FROM SOUTH INDIA. - DR.NOORJAHAN MOHAMMED; DR.S.SUDHA MURTHY; DR. PALANKI SATYA DATTATREYA (International Journal of Pharma and Bio Sciences, 2015)
Quantitative measurement of serum free light chains (S.FLC) has now been adopted into screening algorithms for multiple myeloma (MM). The assay indicates monoclonal free light chain production by the presence of abnormal kappa or lambda free light chain ratio (reference range 0.26-1.65). We report our experience with S.FLC assay in patients of MM in correlation with serum protein electrophoresis (SPE). Review of 50 cases of MM was undertaken. MM was diagnosed in these cases, according to the International Myeloma Working Group (IMWG) criteria. S.FLCs were measured by immunoturbidimetry method, SPE was done on cellulose acetate strip. All 50 cases of MM patients showed abnormal ratio of S.FLCs while SPE could detect monoclonal protein in 44(88%) out of 50 cases. The results indicate that serum FLC analyses have high diagnostic sensitivity and are of additional value in the detection of monoclonal proteins where there is strong clinical suspicion, especially when not detected by SPE.